The Implementation Of The Mandiri Youth Waste Bank In Increasing Economic Status And Community Empowerment In Betawi Village - Muhammad Syahreza; Wahyunengsih (UNUSA Press, 2023)
Abstract Garbage is an incessant problem in everyday life. Every day garbage is always there and increasing. Before the existence of the Independent Youth Waste Bank, the people of Srengseng Paddy were very indifferent to waste. People used to hoard or burn the garbage they have, not infrequently even throw garbage into the river. The purpose of this study is to find out the steps of BSPM in managing waste so that it can be useful and of economic value. This type of research uses a descriptive qualitative approach. Data collection techniques in this study are observation, in-depth interviews, questionnaires and documentation. The technique of checking the validity of the data used in this study is the triangulation technique. Through this article, the author will convey the implementation of the Mandiri Youth Waste Bank in improving the economic status and community empowerment in Betawi Village. Includes planning, implementation, evaluation, follow-up, and impact. As well as supporting and inhibiting factors. The conclusion that can be drawn is that the BSPM program is running well from the statements of 96.7% of customers. Evaluations of the BSPM program include socialization, training in sorting waste, and making compost that has not been effective. The follow-up of the program evaluation is still not effective and efficient. The impact of the BSPM program includes 90% of the sample choosing to be more concerned with the environment, 83.3% of the sample choosing to be aware of the benefits of waste, 60% of the sample choosing to improve the economy, 50% of the sample choosing to add insight, and 30% of the sample choosing to improve skills/ability. The supporting factors for the running of BSPM are the moral support from the RW management, RT management and the community. As well as the inhibiting factors of the BSPM program, namely the absence of tools that can be used to recycle waste from government agencies and poor communication from internal BSPM. Keyword: Waste Bank, Program Implementation, Community Empowerment